ANALISIS TINGKAT PERPUTARAN PIUTANG USAHA TERHADAP LAPORAN ARUS KAS OPERASI PADA MANADO QUALITY HOTEL - Sangka, Sallyritna; Elim, Inggriani; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2018)
Cash flow is the amount of cash flowing in and out of a company within a certain period. The problem raised in this research is how the impact of receivable turnover rate to operating cash flow statement. The method used by researchers using qualitative data. The result of the research shows that the effort of account receivable billing in the year 2015-2016 the worse the billing rate of the accounts receivable and the company need activities that lead to the effort of return of receivables seriously and pay attention to credit sales in order to stay according to established procedure and calculation analysis of cash flow ratio every period necessary to assess the effectiveness of the company's financial statements. Based on the results of research activities of operating cash flow in 2015 of Rp. 2,564,064,056 which means for receivable turnover (RTO) 1.10 times that has exceeded the target company and in 2016 for operating cash flow of Rp. 2,944,637,164 which means for receivable turnover (RTO) 0.89 times so it can not reach the target company.Keywords: Accounts Receivable, Receivable Turnover, Operating Cash Flow